Setting the scene: controversies on trends in mental health among adolescents in the Nordic countries. (30th September 2020) - Eriksson, C; Arnasson, A M; Lyyra, N; Madsen, K R; Torsheim, T; Thorsteinsson, E B; Välimaa, R; Damsgaard, M T; Due, P
Abstract: At present there are different positions regarding trends in adolescent mental health. Can we trust trend data on the mental health among adolescents in the Nordic countries? Some question the trustworthiness of adolescent self-reports, which describe ordinary daily hassles as health complaints, which cannot be interpreted as signs of mental disorders. In addition, today there is a more open climate for talking about mental issues, which can lead to an overestimation of the prevalence of mental disorders. Statistics on mental health services statistics report increased psychopharmaceutic prescriptions as well as consumption of professional care. Such data argues for increased governmental investment in adolescent mental health services. Is this pattern due to increased availability of mental health services and/or increased prevalence of mental health problems in the adolescent population? A concern is that data availability influences policymaking and allocation of resources. If there is an emphasis on self-reported data from adolescents that may an increased risk of medicalization of young people's dealing with their daily lives. If on the other hand the reported problems among young people is disregarded, this would be against the UN Child Convention. The survey data has important qualities especially if the data is analysed and reported properly. The validation of survey measure has been done both regarding psychometric quality and content validity. Advanced analysis of the data can draw a more nuanced picture. Moreover, some screening instruments have been developed as a first step towards making diagnosis. Instead the HBSC surveys ask boys and girls about their health and well-being, social environment and health behaviours. HBSC uses findings at national and international levels to gain new insights into young people's health and wellbeing, understand the social determinants of health, and inform policy and practice to improve young people's lives.